A transportation-location problem model for pedestrian evacuation in chemical industrial parks disasters. (January 2015) - Shen, Yang; Wang, Qingsong; Yan, Weigang; Wang, Jinghong
Abstract: A successful emergency management for chemical industrial parks (CIPs) accidents includes the route and shelter selection. Both of them are based on the collection of chemicals, atmosphere, geographic and population databases of CIPs. This decision process can be considered as a kind of transportation-location problem (TLP). In this paper, a conceptual model of emergency decision system for TLP of CIPs has been reported and a new multi-objective TLP model of pedestrian evacuation has also been proposed. The model includes sub-criteria, and the affected areas are categorized into a priority hierarchy based on human vulnerability model (HVM). The model can be used to design shelter places and guide the evacuation of the affected people. Besides, it can maximize the total time satisfaction level of evacuees combined with the routes passable probabilities. Finally, a case study shows that this model is flexible and applicable to various scenarios and risk measures. Highlights: A conceptual model of emergency decision system for TLP of CIPs is reported. A TLP model combined with human vulnerability, time satisfaction and road passable probability is proposed. A Time-Satisfaction function is proposed to measure the efficiency of the emergency management process.